Public sector accounting and finance : made simple - Adams, Rasheed Alimi (Lagos, Nigeria : Corporate Publishers Ventures, 2001)
Designed primarily for students studying for ICAN Examinations on Public Sector Accounting and Finance or Government Accounting at the Professional Examination I and the ATS part II.
Includes bibliographical references and index.
oif 31/03/15
Loans
Keywords: Finance, Public; Government Accounting